Geochemical signatures of discharge waters, Macraes mine flotation tailings, east Otago, New Zealand - D. Craw; M. Nelson (New Zealand Journal of Marine and Freshwater Research, 2000)
The stream catchment containing the tailings dam complex at the Macraes mine, east Otago, New Zealand has three chemically distinct water types. ( 1) Natural groundwater has pH beween 6 and 8, and sulphate levels locally elevated to 30 ppm. The total carbonate/calcium (Ca) ratio is c. 2, consistent with carbonic acid dissolution of basement schist calcite. Sodium (Na) is strongly elevated over chloride, and these levels are dominated by water‐rock interaction. (2) Decant pond waters lie on two tailings dams, one of which was inactive between 1993 and 1998. Their pH is strongly alkaline (8–9). Sulphate, Na, chloride, and Ca contents are higher than groundwater and these levels have risen steadily over time. Carbonate content is lower than groundwater. Arsenic (As) and iron (Fe) contents are high and variable; arsenic in the active tailings pile is commonly 5–15 ppm. (3) Mixtures of tailings water and natural groundwater (c. 1:1) form from seepage from the upper part of the main tailings pile only and mix beneath the main tailings dam to emerge down stream of the dam. The mixture pH (6.3) is slightly lower than that of the groundwater (mainly >7) whereas the sulphate content is high (>1500 ppm) because of the water component of the tailings. There is no resolvable time lag on the 1‐month scale between discharge of tailings water into the dam and emergence at the foot of the dam. Two distinct water types are identifiable in this setting. Chimney drain discharge is collected in pipes and discharged from those pipes. The tailings component of this water is chemically little different from that which left the tailings. Subsurface flow travels unconfined beneath the tailings dam and interacts chemically with the dam aggregate. Attenuation of Na and chloride, and addition of Ca, carbonate, and magnesium (Mg) occurs. Nearly all dissolved As and copper (Cu) was extracted from the subsurface flow during passage through the dam, whereas some As and all Cu is extracted from the chimney drain discharge. A small volume of a mixture of tailings water and groundwater has continued down stream of the tailings dam complex for c. 50 m in the basement schist as a contaminant plume which took c. 2 years to travel that distance in fractures within the schist. This contaminated water is chemically similar to that of the subsurface flow, and has high sulphate content but no detectable As or Cu.